Methods of microbial control in marine fish larval rearing: clay‐based turbidity and passive larval transfer. (20th January 2015) - Stuart, Kevin; Rotman, Federico; Drawbridge, Mark
Abstract: This study focused on methods to reduce bacterial loads in the larval culture tanks of California yellowtail ( Seriola lalandi ). We conducted two trials to evaluate methods to minimize bacterial loads in the larval rearing water. The first trial examined the use of bentonite clay as a turbidity agent to replace algae in a green water‐type environment. This trial consisted of three treatments: (1) clay with continuous feeding (CCO), (2) clay with batch feedings (CBA) and (3) algae paste with batch feedings (ALG). The results showed that both clay treatments had significantly fewer Vibrio colonies in the water column (CBA – 180 ± 78; CCO – 377 ± 120 CFU mL −1 ) than the ALG treatment (5692 ± 2396 CFU mL −1 ) after 14 days of culture. Survival was significantly higher in the CCO treatment (14.1 ± 2.6%) than either the CBA (2.3 ± 0.5%) or ALG treatments (2.8 ± 1.5%). The second trial attempted to limit bacterial loading in the larval culture tank by passively transferring the larvae into an adjacent, clean tank at 1, 5 and 9 days post hatch during the first 2 weeks of culture. The results from this trial showed that after 12 days of culture, water in the transfertank had fewer Vibrio colonies (1025 ± 541 CFU mL −1 ) than the water in the control tanks (1962 ± 1415 CFU mL −1 ). Also, survival was significantly higher among larvae that were transferred (43.9 ± 13.5%) than in the control tanks (23.1 ± 6.3%).